저소득층 가구의 U-value 및 IAQ 측정을 통한 에너지 효율 개선 사업 효과 분석 - 김서훈(Kim, Seo-Hoon); 김종훈(Kim, Jong-Hun); 정학근(Jeong, Hakgeun); 송규동(Song, Kyoo-dong) (KIEAE Journal, 2017)
Purpose : Currently, the building sector accounts for about 24% of total domestic energy use. There is a growing need for building energy efficiency. In particular, in low-income households, the energy efficiency of the buildings is very low due to the characteristics of the aged buildings, resulting in an increase in heating costs and maintenance costs, resulting in an increase in fuel cost / current income ratio. In terms of energy saving of buildings, the energy efficiency improvement project for low-income households is to improve energy-efficient buildings by improving the insulation performance of the outer cover and improving the performance of the equipment. In order to improve the energy efficiency improvement projects and policies of low-income households, it is necessary to accurately diagnose the present condition of the support target households. Method : In this study, through the precise diagnosis of the building wall, numerical measurement and review of the poorest part in the actual building is conducted numerically, and then the building is insulated so that it can be carried out within the actual budget range. In addition, indoor air quality (CO2 concentration, formaldehyde, volatile organic compounds) was measured through simple analysis of the air environment in the actual residence space, and the effect of improving the residential environment before and after construction was analyzed. Result : The analysis of wall insulation performance data was analyzed to quantitatively analyze areas where the wall insulation performance was weak and to improve (repair, replace, insulate) buildings.